Acral Cutaneous Neural Angiomatous Hamartoma: A Variant of Palmar Cutaneous Hamartoma? - Nebojsa Arsenovic; Anuradha Sheth (Case Reports in Dermatological Medicine)
Hamartomas are benign malformations composed of tissue elements normally found at that site, but which are growing in a disorganized fashion. Cutaneous hamartomas containing only neural and/or neurovascular elements are very rare, with very few case reports in the literature. Herein we describe a case of congenital neural angiomatous hamartoma of the skin.